SISTEM INFORMASI AKUNTANSI PELAYANAN JASA RAWAT JALAN DAN RAWAT INAP PADA RUMAH SAKIT UMUM MITRA SEJATI MEDAN - Lisna Hutahean; Edison Sagala; Jamaluddin Jamaluddin (Universitas Methodist Indonesia, 2020)
This study aims to examine both the application and the accuracy of accounting information system on outpatient and inpatient service at Medan General Hospital of Mitra Sejati. The research method used is descriptive method using secondary data, in which the obtained data come from existing sources such as the profile of Medan General Hospital of Mitra Sejati, organizational structure, flowchart and reports of outpatient and inpatient service at Medan General Hospital of Mitra Sejati. Based on the results of this research, it can be concluded that the accounting information system for outpatient service at Medan General Hospital of Mitra Sejati has not been effectively executed. There are a great number of mistakes made by medical staffs in inputing patient data. Accordingly, in the future Medan General Hospital of Mitra Sejati can provide training for employees in using the accounting information system effectively and is expected to improve outpatient and inpatient service to avoid errors which will impact the quality of service in the hospital.